PERAN PEMERINTAH DESA DALAM PEMBERDAYAAN MASYARAKAT MELALUI PAGUYUBAN ALAS KAKI, STUDI KASUS DESA MEDALI, KECAMATAN PURI KABUPATEN MOJOKERTO - Abdul Basith, Mohammad Resi; Arisandi, Rachman Sidharta; Suprapto, Suprapto (PAWITRA KOMUNIKA : Jurnal Komunikasi dan Sosial Humaniora, 2025)
In recent years, the empowerment and planning system of the village government together with the community with the government system in Indonesia is based on law number 6 of 2014 concerning Villages, which explains that a village regulation can be implemented by the village regarding its existing policies in its own area. Minister of Home Affairs issued Regulation Number 114 of 2014 concerning Village Development Guidelines. Article 1 Number 114 of 2014 concerning Guidelines for Development and planning through village empowerment states that, Village development is an effort to improve the quality of life and life for the greatest welfare of village communities. Cooperation or synergy between the government and the community in the context of development for economic prosperity as stated in mutual cooperation does not only require the role of the village government or the community itself, but also our shared role between the village government and the community which can be seen in various kinds of activities, including work. community service, village competitions, physical development in the form of infrastructure, as well as training in productive economic activities aimed at increasing knowledge and skills for the development of productive economic businesses for village communities. In this research, the researcher formulated the problem of how the village government synergizes with the community in developing innovative villages.